2019
DOI: 10.1080/13683500.2019.1578340
|View full text |Cite
|
Sign up to set email alerts
|

Guanxi or weak ties? Exploring Chinese diaspora tourists’ engagements in social capital building

Abstract: Most of existing studies assume that diaspora tourism can facilitate the tourists to reconnect socially to their ancestral home. Yet, how and why diaspora tourists engage in social capital building during their home return trips is still uncertain. Whether they feel socially connected and which groups they are more likely to build connections with are unknown. This study explores the ways in which diaspora tourists foster and sustain social capital by focusing on the case of Chinese immigrants and descendants.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…Fourth, sociological perspectives of diasporic return. Future research could also extend discussions on migrants' social engagements, in terms of how different social contexts and diaspora's interactions with their significant others help to shape the tourists' experiences; how home return travel experience influences local and transnational social networks and social capital building (Li, 2019;Lew & Wong, 2004;Zhou & Lee, 2015). This avenue offers a promising path forward by engaging more sociological debates over the complex relationships between diasporas, transnationalism, and social networks.…”
Section: Future Research Agendamentioning
confidence: 99%
“…Fourth, sociological perspectives of diasporic return. Future research could also extend discussions on migrants' social engagements, in terms of how different social contexts and diaspora's interactions with their significant others help to shape the tourists' experiences; how home return travel experience influences local and transnational social networks and social capital building (Li, 2019;Lew & Wong, 2004;Zhou & Lee, 2015). This avenue offers a promising path forward by engaging more sociological debates over the complex relationships between diasporas, transnationalism, and social networks.…”
Section: Future Research Agendamentioning
confidence: 99%
“…Unlike in North America, Bian and Ang (1997) find that even if weak ties are not as intensely emotive as strong ties, weak ties between job seekers and intermediaries are just as effective for matching individuals to jobs as strong ties. Li (2020) expands on this with a study of Chinese diasporic tourists visiting China, observing that weak ties between tourists and local communities help build the foundation for social mobility and connect with even more communities in the future. Indeed, weak ties at their core represent a kind of social capital that breeds more social capital, which has been essential for navigating social and work life in China's unique labor market from its modern founding to the present (Bian 1997;Blau and Ruan 1990;Burt and Burzynska 2017;Nee and Opper 2012).…”
Section: Theorizing Tie-formation In Sns Network: Toward Assortation ...mentioning
confidence: 96%
“…Among authors who have applied Granovetter’s (2009) ideas about coupling and decoupling in their studies (Busch and Barkema, 2020; Corrêa et al , 2018; Li, 2020; Sommer and Gamper, 2018), Corrêa et al (2018) investigated the influence of religious entrepreneurs’ coupling and decoupling on the trajectory of their institutions. Ultimately, they concluded that pastors and their congregations seem capable of striking a balance in their social structure, particularly by supporting each other in dense networks of mutual solidarity (Corrêa et al , 2018).…”
Section: Theoretical Backgroundmentioning
confidence: 99%